The diagnostic performance of microRNAs expression levels in cellular aspirate of solitary thyroid nodule overrides that of cytology - Hussein, Tawfik Ahmed T.; Hafez, Emad Eldein M. Abdel; Marie, Yasmin M.; Elbalshy, Abdel Latif; Habashy, Omnia Y. (International Surgery Journal, 2023)
Background: Evaluation of the diagnostic performance of estimated expression levels of microRNAs 203a, 206 and 576 in the cellular aspirate of solitary thyroid nodule (STN) in comparison to cytological examination for identification of malignant TN. Methods: The 74 patients with STN underwent clinical and US evaluation and gave blood samples for estimation of serum levels of thyroglobulin (TG) and anti-thyroglobulin antibodies (ATG). Then, fine-needle aspiration was performed to obtain cellular aspirate for cytological examination and estimation of levels of microRNAs. The appropriate surgical procedure was undertaken and the excised specimens were sent for pathological diagnosis. Results: Pathologically, 19 nodules had papillary thyroid carcinoma (PTC), 6 nodules had follicular carcinoma and one medullary carcinoma, while 48 nodules were benign nodules. Cytological examination diagnosed malignancy in 5 specimens, while specimens were suspicious of malignancy, 25 specimens were diagnosed as benign and 14 specimens as non-diagnostic. Serum levels of TG and ATG were significantly higher with malignancy. Expression levels of miR-203a and 206 were significantly lower, while miR-576 were significantly higher in malignant than benign aspirates. Multivariate regression analysis showed more significant ability for miR-576 level than cytological examination as screening and for miR-203a than miR-206 as diagnostic for malignant aspirate and for PTC Conclusions: Estimation of expression levels of microRNAs in cellular aspirate of STN is feasible and accurate for detection of the malignancy. Down-expression of miR-203a and over-expression of miR-576 in tissue aspirate are more diagnostic for TC and can specify PTC cases out of other TC cases.